في العراق Chrozophora tinctoria L دراسة الصفات المظهرية والتشريحية ودراسة البيئة والتوزيع الجغرافي للنوع - الدبيسي, اسراء عبد الرزاق مجيد (Al-Nahrain Journal of Science, 2013)
Abstract:Morphology, Anatomy, Ecology and Geographical distribution studies on the species Chrozophora tinctoria L. were carried out which showed that the plants are annual herbs or sub shrubs, branched dichotomously from the semi-woody base, covered with stellate and simple pointed hears. The plant contains simple stipulated leaves each has pair of basal glands. It is monoecious with unisexual flowers arranged in panicls of mixed infloriecens, male flower enclosed by five green lanceolated calyx leaves and five yellow lanceolated and united petale leaves with monadelphous stamens. Female flowers are enclosed by ten leaves similar to the calyx leaves of male flowers and have one compound pistil. Fruit is capsule schizocarpic with three seeds. Anatomically, the study showed that the druses crystal distributed at all plant parts, leaves are bifacial with simple uniseriate epidermis, the characters and composition of stem tissues are similar to petiole tissues. Ecologically, the plant is grown in different soils with different ecosystems and distributed in all Iraqi districts. Results are supported with photographs and graphics.